2023
DOI: 10.1039/d2ta09068f
|View full text |Cite
|
Sign up to set email alerts
|

Rarely negative-thermovoltage cellulose ionogel with simultaneously boosted mechanical strength and ionic conductivity via ion-molecular engineering

Abstract: Excellent mechanical strength and conductivity are essential and exigent features for advanced gel materials. The trade-off between them, however, remains a challenge. Here, we proposed an ion-molecular engineering strategy to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…The X‐ray diffraction (XRD) results demonstrate that the cellulose I crystal allomorph of the cellulose pulp was disrupted by IL, confirming the dissolution of cellulose chains. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…The X‐ray diffraction (XRD) results demonstrate that the cellulose I crystal allomorph of the cellulose pulp was disrupted by IL, confirming the dissolution of cellulose chains. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…The Ni–Cl–M displayed a negative Seebeck coefficient of −7.2 mV K −1 , attributed to the hygroscopic nature of BTAC and the large difference in the sizes of the cationic vs anionic groups. As Chen et al 48 and Hu et al 49 suggested that electrolytes with large cationic but smaller anionic groups are ideal for negative TE materials, the negative Seebeck coefficient of Ni–Cl–M is attributed to the hygroscopic nature of BTAC and large difference in the sizes of cationic vs . anionic groups.…”
Section: Resultsmentioning
confidence: 99%
“…[95] Li et al developed a ZnCl 2 doped cellulose ionogel, supporting the movement of small anions while limiting the movement of large cations. [96] Excitingly, the prepared thermoelectric device can generate useful electricity (≈110 mV) by using low-grade thermal source generated by solar irradiation.…”
Section: Ionogel Electrolytes In Thermoelectric Devicesmentioning
confidence: 99%